Efektivitas Sari Buah Belimbing Wuluh (Averrhoa Bilimbi Linn) sebagai Larvasida Alami terhadap Nyamuk Aedes sp. - Reni Yunus; Afrindayanti Afrindayanti; Petrus Petrus (Poltekkes Kemenkes Kendari, 2018)
Bilimbi (Averrhoa Bilimbi Linn) is a plant that commonly used as a daily cooking spice. A. Bilimbi has the potential as a larvicide, as it containing alkaloids, saponins, and flavonoids. This study aimed to determine the effectiveness of A. Bilimbi juice as a larvicide for Aedes sp. This research was an experimental laboratory study with a post test only control group design, the objects were divided into two groups, the treatment group and the control group. Total samples was 350 larvae of Aedes sp.. The results showed that the effectiveness of the A. Bilimbi juice on the death of Aedes sp. larvae within 24 hours was ineffective at concentrations of 2%, 3%, and 4% while effective at concentrations of 5%, 6%, 7%, and 8%. The calculation of probit model showed that the value of LC50 is 4.080% and LC90 is 7.014%. A. Bilimbi juice is effective as a natural larvicide for the Aedes sp.